Characterization of Chitosan Isolated from Shrimp Shell Waste and Its Ability to Preserve White Tofu - Bahri, Syamsul; Fadilah, Nur; Hanafi, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The research has been conducted to characterize chitosan isolated from shrimp shell and also to determine the ability of chitosan in preserving organoleptic parameters of white tofu. Isolation of chitin was performed through two stages, namely deproteination and demineralization. Chitosan is obtained by adding NaOH on chitin in deacetylation process. The obtained chitosan was characterized using several methods. Molecular weight of obtained chitosan is 15 kDa with the degree of deacetylation is 80.3%, whereas analysis of water level, ash, and protein content are 0.3%, 32.1%, 3.79% in consecutively. The optimum concentration to preserve organoleptic parameters of white tofu is 15 minutes in 1% of chitosan.